STRATEGI PEMBIASAN GURU PAI DALAM MENGATASI KESULITAN BELAJAR PESERTA DIDIK PADA MATERI SALAT : (Studi di UPT Satuan Pendidikan SDN Cangkringmalang III Beji Pasuruan) - Afriyanti, Naning; Rofiq, Ainur (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
One of the challenges faced by Islamic religious education teachers in the current era is the spiritual crisis of students is the difficulty in understanding the prayer material that has been explained and taught. One of the tactics used in the SDN Cangkringmalang III Beji Pasuruan is the habituation strategy. The purposes of this study are to 1) analyse the forms of learning difficulties experienced by students in prayer material 2) analyse the teacher's habituation strategy in overcoming students' learning difficulties in prayer material, 3) analyse the factors that support and hinder habituation strategies in overcoming learning difficulties of students in prayer material at SDN Cangkringmalang III. The type of research used in this research is descriptive qualitative approach. And the data collection techniques used are observation, interviews, and documentation. The results showed that the difficulties experienced by students were reciting the prayer recitation, remembering the prayer material. While the strategy used is a habituation strategy by reciting prayer recitations and performing dhuha and duhur prayers together at school. While the factors that cause student difficulties are family factors, environmental factors and motivation.